Husserl e la storia della filosofia. Descartes come caso di studio esemplare - Franchini, Stefano (Bollettino Filosofico, 2024)
In this article, I will reflect on Husserl’s references to Descartes’ philosophy. My aim is to show why Descartes can be considered an exemplary case within Husserl’s investigations on history of philosophy. In the first part, I will consider the image of Descartes in Husserl’s philosophy, which remains virtually unchanged until his late work. Then I will stress the ambivalence that runs through Husserl’s evaluation of the French philosopher. In the second part of this article, after discussing the meaning of Husserl’s Dichtung der Philosophiegeschichte and Crisis’ zig-zag method, I will debate the reasons behind the corrections Husserl makes to Descartes’ thought. Finally, in the third session, I will show Descartes’ function for the philosophy of the present. Keywords: Cogito, Descartes, History of Philosophy, Husserl, Idea of Philosophy